RADIOGRAFI UNTUK PERAWATAN IMPLAN GIGI - Hanna H. Bachtiar Iskandar; Menik Priaminarti; Suhandi Sijaya (Faculty of Dentistry, Universitas Indonesia, 2015)
Dental implants have become an accepted form of permanent tooth replacement. Successful dental implant treatment requires knowledge of the precise location in connection with critical structures in maxillae and mandible. Injurty to the nerve canal or perforation of maxillary antrum can cause paresthesia or antral infection that may lead to failure of the treatment. Measuring the height and width of residual alveolar ridge is necessary to select the appropriately sized implant as well as to assure the adequacy of bone. Presurgical radiographic evaluation of dental implants plays very important role in the success of implant treatment procedure. Various imaging modalities from conventional intraoral radiographs to more sophsticated and modern ones can be used for this purpose. The conventional imaging modalities have very limited diagnostic information in accordance with details and accurate in bone evaluation of the implant sites. On the other hand, modern imaging modalities such as Dental CT have been proven to produce excellent image either for measuring the detailed evauating the sites. Selecting the appropriate imaging modality will be one of the key to success in dental implant treatment.